PROBLEMTIKA HUKUM CADAR DALAMISLAM: SEBUAH TINJAUAN NORMATIF-HISTORIS - Lisa Aisiyah Rasyid; Rosdalina Bukido (IAIN Manado, 2018)
Cadar (veil) as part of the Islamic Shari'a, has always been a controversial issue among Muslims. In the study of Islamic interpretation itself the arguments governing the obligation or the absence of the cadarare still disputed. So that, this paper aims to examine the various views of Muslim scholars and commentators on the law of wearing cadar for Muslim women without regard to the normative and historical side of that usage. Most of them argue that the use of cadar normatively may become mandatory in a region, if it has become a collective agreement and become a socially acceptable norm. While in certain environments, not using a cadar may be better if it is intended to reject mudharat. This may occur because historically the command of